(untitled) (Revista Espinhaço, 2019)
This paper organizes information from different sources on the presence of viticulture in the region of Diamantina, Minas Gerais state, Brazil. This region is recognized since the eighteenth century for its outstanding economic potential for this cultivation, due to its characteristic terroir. Recovering the trajectory of this activity, between the beginning of the nineteenth century and the end of the 1960s, when it was interrupted, we seek to reflect on the previous attempts of implementation and economic viability of the wine industry in the region and a tentative balance of its results in the period. In the context of the recovery of the Alto Jequitinhonha wineries, starting in 2004, rescuing the previous trajectory can contribute to the development and innovation in the regional winery and wine tourism production chain.